Методы математической физики. Специальные функции. Уравнения математической физики рабочая тетрадь учебное пособие для вузов - Багров физик профессор Томского государственного университета; Белов; Задорожный математик доцент Томского политехнического университета, кандидат физико-математических наук; Трифонов российский физик, математик профессор Томского политехнического университета, доктор физико-математических наук (Изд-во ТПУ, 2012)
This workbook complements the theoretical material presented in the textbook on Special Functions and Equations of Mathematical Physics. The workbook contains examples for solving on the topics involved in the textbook and individual tasks (30 variants) to be solved without assistance. The textbook can be useful to the graduate students, magisters, and postgraduates specializing in theoretical and mathematical physics. The textbook is intended for students and post-graduates of physical and engineering departments.